Pendekatan Budaya dan Agama dalam Penanganan Pandemi Covid-19 di Bali dan Jawa Tengah - Anta Ibnul Falah; Pande Made Kutanegara; Agus Heruanto Hadna (Balai Penelitian dan Pengembangan Agama Semarang, 2022)
The Covid-19 pandemic causing a multidimensional crisis has become a serious challenge to the quality of leadership, including leadership at the provincial level. This study was intended to compare the leadership of Bali and Central Java in utilizing culture to handle the pandemic and to identify the dominant style the two leaders applied. This study was conducted using the library method by utilizing related secondary data. The data was presented comparatively between Bali and Central Java, to identify differences and/or similarities. The results of the study show that leadership in both regions makes extensive use of local culture as part of a strategy for dealing with a pandemic. Balinese leadership utilizes culture such as Tri Hita Karana according to Hindu teachings, while Central Javanese leadership utilizes a culture of solidarity that is in line with the concept of Hablumminannas in Islam. The style similarities by the two leaders are collaborative and transformational, while the difference is shown in serv- ing style that was only identified in Central Java. With these styles, the two leaders emphasized not only rigid regulations but also an equal relationship, so that they have succeeded in including local culture to handle the pandemic. The socio-economic implications of the pandemic in Bali and Central Java are also discussed in this study.